1990
DOI: 10.1177/38.6.2159498
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural localization of phosphatase activity in the guinea pig pineal gland by the cerium technique.

Abstract: Thiamine pyrophosphatase (TPPase), nucleoside diphosphatase (NDPase), and glucose-6-phosphatase (G-6-Pase) were localized by the cerium technique in guinea pig pinealocytes and compared with the corresponding lead technique. NDPase and TPPase were also compared at different pH values using the cerium technique. Vibratome sections of perfusion-fixed tissue were incubated with cerium chloride or lead nitrate. Substrates used were thiamine pyrophosphate (for TPPase), sodium inosine diphosphate (NDPase), and disod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…In spermatocytes, all ER cisternae displayed G6Pase activity similar to the ER reactivity observed in Leydig cells, Sertoli cells and other cell types [19,22,41]. In contrast, the ER of spermatids was not uniformly labeled with cerium since some of the ER cisternae distal to the Golgi apparatus were G6Pase-positive, while others were either slightly reactive or negative.…”
Section: G6pase Activity In Ersupporting
confidence: 58%
See 2 more Smart Citations
“…In spermatocytes, all ER cisternae displayed G6Pase activity similar to the ER reactivity observed in Leydig cells, Sertoli cells and other cell types [19,22,41]. In contrast, the ER of spermatids was not uniformly labeled with cerium since some of the ER cisternae distal to the Golgi apparatus were G6Pase-positive, while others were either slightly reactive or negative.…”
Section: G6pase Activity In Ersupporting
confidence: 58%
“…In addition, the consistency of the G6Pase activity in acidic, neutral or slightly alkaline media minimized the possibility raised by Tokunaga et al [41] that the reactivity observed in the Golgi apparatus may be due to acid phosphatases, which are known to be present in the Golgi apparatus of spermatids in particular [4,38,39]. Recent results obtained by Luo et al [22] on the ultrastructural localization of various phosphatases in cells of the pineal gland also tend to validate the use of the cerium technique in the cytochemical localization of phosphatases.…”
Section: Value ~F the Cerium Technique For The Ultrastructural Localmentioning
confidence: 95%
See 1 more Smart Citation
“…Thiamine pyrophosphatase is generally considered to be a cytochemical marker for the trans side of the Golgi complex in many cell types (Cheetham et al 1971;Angermüller und Fahimi 1984;Roth et al 1985;Luo et al 1990). Our data demonstrate that FRP due to thiamine pyrophosphatase activity was not only present in trans side cisternae but also in medial and cis side cisternae of Golgi complexes in acinar cells of unfixed rat parotid glands (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For the detection of 5′-nucleotidase and thiamine pyrophosphatase activities in liver and parotid gland which were freshly fixed or fixed after freezing and thawing, the tissue blocks were preincubated in media containing 100 mM TRIS-maleate buffer (pH 7.2), 2 mM CeCl 3 , and 2 mM MgCl 2 or 100 mM TRIS-maleate buffer (pH 7.2), 2 mM CeCl 3 , and 2 mM MnCl 2 for 30 min at 22° C, respectively (Luo et al 1990), followed by incubation for 30 min at 37° C in complete incubation media in the presence of 1 mM AMP or 1 mM TPP, respectively. All steps were performed under gentle continuous shaking.…”
Section: Methodsmentioning
confidence: 99%